The Greenlife company: a teaching case study in management. (2018) - Scott, Joseph; Ross, William H.
The Greenlife company is a US family-owned business specialising in home improvement projects. One division sells and installs energy-efficient replacement windows. The small business owner must address problems relating to the work habits of two sales representatives. One is experienced, but his lack of communication with window installers creates scheduling problems. The other is new and has trouble estimating when materials will arrive and how long installation will take. Additionally, the telephone messaging and scheduling systems are antiquated, yet the experienced sales representative opposes changes. The owner also decides that the compensation system does not adequately motivate the sales representatives. The case offers students an excellent opportunity to apply organisational behaviour and information systems concepts when grappling with these problems.